The Analysis of the Partnership Implementation of Plasma Broiler Chicken Breeders and Core Companies (Case Study of Farming Broiler Chicken in Kendari City) - La Ode Arfan Dedu; Hartina Batoa; Musram Abadi Musram Abadi; Hadi Sudarmo; Vit Neru Satrah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The problem sometimes encountered in partnership relations is the implementation of non-mutually beneficial partnerships between the core company and the plasma breeder. This occurs because the company has a stronger bargaining position than the breeder regarding capital, technology, markets, and management. So it is the company that determines the price at the breeder level, and the company also determines the price in the market. This has caused the company to control the price of broiler chickens in markets in Kendari City, thus enabling the development of a cartel to manage broiler chickens from upstream to downstream. In the long run, this research aims to improve the quality of the partnership relationship between companies and breeders in Kendari City. Especially the aims of this study are: 1) to describe the implementation of the partnership that the company is carrying out as the core with the breeder as the plasma, and 2) to analyze the income of the plasma breeder. This research was carried out in August–October 2022, and the research location was in Kendari City, Southeast Sulawesi Province. The sampling technique was a purposive method. The implementation of the partnership between the plasma breeder and the core company was analyzed using descriptive analysis. In contrast, the breeder's income level was analyzed using income analysis and R/C ratio analysis. The results showed that implementing the plasma breeder partnership and the core company was going well per the contract agreement. The income earned by the breeder in 1 production period is IDR 3,637,394, and the R/C ratio is 1,043, which means that the R/C ratio is greater than 1, so that partnership between the plasma breeder and the core company provides benefits for the breeder.